Pengaruh Profitabilitas, Likuiditas dan Ukuran Perusahaan terhadap Return Saham pada Perusahaan Manufaktur di Bursa Efek Indonesia - Wulandari, Putri (Media Akuntansi Perpajakan, 2025)
Abstrak The purpose of this study is to analyze the effect of profitability, liquidity and company size on stock returns. The study was conducted on manufacturing companies listed on the Indonesia Stock Exchange for the period 2015–2024. Profitability uses the return on equity proxy. Liquidity uses the current asset proxy. Company size uses the Ln total asset proxy. While stock returns use the proxy for changes in stock prices this year compared to last year. using the price to book value proxy. The data analysis method used is multiple linear regression, to test the effect of liquidity, profitability and company size variables on stock returns. The analysis stages consist of descriptive statistics, selecting the best model, classical assumption tests, and multiple regression tests to prove the research hypothesis. The results of the study indicate that profitability with the return on equity proxy has no effect on stock returns, which means that return on equity is not a predictor for predicting stock returns. Meanwhile, liquidity with the current ratio proxy and company size have a significant effect on stock returns. The implication is that liquidity and company size can be the main considerations for investors in assessing the performance of a company's shares. This finding indicates that investors focus more on the liquidity aspect than profitability in making investment decisions.